Encapsulation of Luminescent Gold Nanoclusters into Synthetic Vesicles - Regina M. Chiechio; Solène Ducarre; Célia Marets; Aurélien Dupont; Pascale Even-Hernandez; Xavier Pinson; Stéphanie Dutertre; Franck Artzner; Paolo Musumeci; Célia Ravel; Maria Jose Lo Faro; Valérie Marchi (Nanomaterials, 2022)
Gold nanoclusters (Au NCs) are attractive luminescent nanoprobes for biomedical applications. In vivo biosensing and bioimaging requires the delivery of the Au NCs into subcellular compartments. In this view, we explore here the possible encapsulation of ultra-small-sized red and blue emitting Au NCs into liposomes of various sizes and chemical compositions. Different methods were investigated to prepare vesicles containing Au NCs in their lumen. The efficiency of the process was correlated to the structural and morphological aspect of the Au NCs’ encapsulating vesicles thanks to complementary analyses by SAXS, cryo-TEM, and confocal microscopy techniques. Cell-like-sized vesicles (GUVs) encapsulating red or blue Au NCs were successfully obtained by an innovative method using emulsion phase transfer. Furthermore, exosome-like-sized vesicles (LUVs) containing Au NCs were obtained with an encapsulation yield of 40%, as estimated from ICP-MS.